2018
DOI: 10.1080/07481187.2018.1503621
|View full text |Cite
|
Sign up to set email alerts
|

Lived experience of a child’s chronic illness and death: A qualitative systematic review of the parental bereavement trajectory

Abstract: To understand the lived experience of parents who have lost their child to a chronic life-limiting condition, six major databases were searched by adhering to the PRISMA guidelines. Articles were screened for appropriateness using the SPIDER tool, and relevant qualitative studies were selected for full-text data analysis using Thematic Synthesis. Findings were categorized into 13 themes that were further organized into a four-phase trajectory of parental bereavement experience of child loss, namely: Liminal Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 53 publications
5
34
0
Order By: Relevance
“…Findings from this Asian study where participants were of predominantly Chinese origin, followed by Malay and Indian origin, build on our previous work in parental bereavement which focused on participants from a Western context [25]. An important contribution of the present study is its value-addition to the literature on family support for parent-caregivers and bereaved parents.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Findings from this Asian study where participants were of predominantly Chinese origin, followed by Malay and Indian origin, build on our previous work in parental bereavement which focused on participants from a Western context [25]. An important contribution of the present study is its value-addition to the literature on family support for parent-caregivers and bereaved parents.…”
Section: Discussionsupporting
confidence: 55%
“…For bereaved parents, ritualization following child death can help to mediate grief through maintaining continuing bonds with their deceased child, providing a sense of control and offering a means of posttraumatic growth by honoring and memorializing their child [24]. Dutta et al explored the lived experience of parental bereavement due to a child's chronic life-threatening illness and subsequent death in a qualitative systematic review of 25 high-quality articles published between 2000 and 2017, and highlighted that there were no Asian studies conducted on the parental bereavement experience stemming from a child's death due to chronic illness [25]. This means that the unique needs and concerns of Asian bereaved parents remains unknown, creating a knowledge gap in the delivery of to Asian parents.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from this study build on our previous work in parental bereavement [25]. However, contrary to our previous dataset, which was derived from western populations, participants in this study were of predominantly Chinese origin, followed by Malay and Indian origin.…”
Section: Theme 7: Holistic Healthcare Approachsupporting
confidence: 54%
“…[Insert Table 1 here] These findings echo previous literature that parents facing potential child loss could benefit from psychosocial and therapeutic interventions as early as prognosis and throughout the illness trajectory, which could ease the transition from caregiving, through mortality and bereavement [9,[11][12][13], thus mitigating adverse grief outcomes [14]. However, most supportive interventions for parents caring for children with chronic life-threatening illness only occur after bereavement [15][16][17], and a recent systematic review found negligible evidence to support their effectiveness [18].…”
Section: Parental Bereavement Trajectories Of Child Losssupporting
confidence: 78%
“…Our research team recently conducted a qualitative systematic review of 25 high-quality research articles published between 2000 and 2017, exploring the lived experience of parental bereavement due to a child's chronic life-threatening illness; a four-phase parental bereavement trajectory of child loss was developed, highlighting appropriate interventions that help parents identify care needs, elicit caregiving strengths, enhance death preparedness, and foster meaning-making throughout the illness trajectory in order to reduce psycho-emotional distress during end-of-life and into bereavement [9].…”
Section: Parental Bereavement Trajectories Of Child Lossmentioning
confidence: 99%